2005
DOI: 10.1385/endo:26:3:301
|View full text |Cite
|
Sign up to set email alerts
|

Oogenesis in Adult Mammals, Including Humans: A Review

Abstract: The origin of oocytes and primary follicles in ovaries of adult mammalian females has been a matter of dispute for over 100 yr. The prevailing belief that all oocytes in adult mammalian females must persist from the fetal period of life seems to be a uniquely retrogressive reproductive mechanism requiring humans to preserve their gametes from the fetal period for several decades. The utilization of modern techniques during last 10 yr clearly demonstrates that mammalian primordial germ cells originate from soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
133
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 92 publications
(139 citation statements)
references
References 55 publications
0
133
1
5
Order By: Relevance
“…In fetal ovaries, with the support of the immune system related cells, secondary germ cells arise from the somatic OSC. The OSC have been implicated in the formation of oocytes (Allen, 1923;Evans and Swezy, 1931;Everett, 1943;Bukovsky et al, 1995;Bukovsky et al, 2004;Bukovsky et al, 2007), and it also has been suggested that they are a source of granulosa cells (Brambell, 1927;Motta et al, 1980;Bukovsky et al, 1995;Bukovsky et al, 2004;Bukovsky et al, 2005a). As already indicated, numerous small germ cells (10 lm in diameter) are present in OSC layer of human fetal ovaries from 7 to 24 weeks of intrauterine life (Motta and Makabe, 1986).…”
Section: Establishment Of Osc Niche In Embryonic Ovariesmentioning
confidence: 97%
See 4 more Smart Citations
“…In fetal ovaries, with the support of the immune system related cells, secondary germ cells arise from the somatic OSC. The OSC have been implicated in the formation of oocytes (Allen, 1923;Evans and Swezy, 1931;Everett, 1943;Bukovsky et al, 1995;Bukovsky et al, 2004;Bukovsky et al, 2007), and it also has been suggested that they are a source of granulosa cells (Brambell, 1927;Motta et al, 1980;Bukovsky et al, 1995;Bukovsky et al, 2004;Bukovsky et al, 2005a). As already indicated, numerous small germ cells (10 lm in diameter) are present in OSC layer of human fetal ovaries from 7 to 24 weeks of intrauterine life (Motta and Makabe, 1986).…”
Section: Establishment Of Osc Niche In Embryonic Ovariesmentioning
confidence: 97%
“…1C) entering the rete channels (black and dotted arrowheads, Fig. 1D) are committed by interaction (white arrowhead) with resident memory cells (asterisk; Bukovsky et al, 2005a). Such committed cells (c and cT, Fig.…”
Section: Establishment Of Osc Niche In Embryonic Ovariesmentioning
confidence: 99%
See 3 more Smart Citations